2018
DOI: 10.3892/ol.2018.9297
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the expression and function of myeloid differentiation factor 88 in human osteosarcoma

Abstract: The aim of the present study was to investigate the expression and function of myeloid differentiation factor 88 (MyD88) in osteosarcoma. Immunohistochemical staining was used to detect MyD88 protein in osteosarcoma tissues and matched normal bone tissues. The association between MyD88 expression and the clinical characteristics of patients with osteosarcoma was analyzed. Furthermore, survival analysis of patients with osteosarcoma was performed to study the association between MyD88 expression and patient pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Though MyD88 does not have any catalytic activity, its activation causes dimerization leading to the activation of downstream kinases (10). It has been shown that the progression of signaling pathways occur due to the phosphorylation of two key adaptor proteins IRAK1 and TAK1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though MyD88 does not have any catalytic activity, its activation causes dimerization leading to the activation of downstream kinases (10). It has been shown that the progression of signaling pathways occur due to the phosphorylation of two key adaptor proteins IRAK1 and TAK1.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical TLR signaling has been reported to be regulated by an array of molecules through various mechanisms to adjust the consequences of associated autoimmune and inflammatory diseases. In the canonical pathway, for most of the TLRs, upon ligand activation, MyD88 is recruited as a dimer in the cytoplasmic TIR domain in a homophilic interaction (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Though, MyD88 does not have any catalytic activity, its activation causes dimerization leading to the activation of downstream kinases (Chen et al, 2018). It has been shown that the progression of signaling pathways occur due to the phosphorylation of two key adaptor proteins IRAK1 and TAK1.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical TLR signaling has been reported to be regulated by an array of molecules through various mechanisms to adjust the consequences of associated autoimmune and inflammatory diseases. In the canonical pathway, for most of the TLRs, upon ligand activation, MyD88 recruited as a dimer in the cytoplasmic TIR domain in a homophilic interaction (Chen et al, 2018; Loiarro et al, 2010; Noursadeghi et al, 2008; Jia et al, 2014; Hsiao et al, 2014; Han et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…That resulted in the inhibition of interleukin 1 beta-mediated activation of NF-κB activity [ 11 ]. Preclinical studies have demonstrated the antitumor activity of ST2825 in multiple types of malignancies such as lymphoma, leukemia, and osteosarcoma [ 12 , 13 ]. However, neither the pathological role of MyD88 nor the treatment effect of ST2825 is currently under investigation in MM.…”
Section: Introductionmentioning
confidence: 99%